2011
DOI: 10.1057/jdhf.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Gold stocks, the gold price and market timing

Abstract: We investigate the relationship between gold prices and gold equity index levels and consider whether this offers any explanatory power for the future returns of gold stocks. It is observed that a simple, well-specified model can explain movements in the stock prices of gold-producing firms. Using evidence from gold exchange-traded funds, we also show that investors' market timing decisions have reduced their average returns from these instruments by over 1.5 per cent annually between 2005 and 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Mishra et al (2010) have shown a positive relation between gold prices and equity markets in India, and also confirmed that both equity returns and gold prices are essential for predicting each other. Gwilym et al (2011) have conducted an important research on the association of equity returns and changes in gold prices and explicated the illustrative influence of gold rates with respect to future return to gold investment. Samadi et al (2012) studied the causal relationship between inflation, gold price, oil prices, exchange rate, and equity returns of the Tehran Stock Exchange.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mishra et al (2010) have shown a positive relation between gold prices and equity markets in India, and also confirmed that both equity returns and gold prices are essential for predicting each other. Gwilym et al (2011) have conducted an important research on the association of equity returns and changes in gold prices and explicated the illustrative influence of gold rates with respect to future return to gold investment. Samadi et al (2012) studied the causal relationship between inflation, gold price, oil prices, exchange rate, and equity returns of the Tehran Stock Exchange.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the sensitivity of gold stocks to the gold price is not constant. Tufano (1998) documents that there is substantial cross‐sectional and times series variation in the gold betas of the gold mining companies (see also Gwilym et al, 2011). He proposes a theoretical model where the gold price exposure is negatively related to the gold price, the gold price volatility, the diversification (i.e., the extent to which the firm has activities except for mining), and the hedging activities, and positively related to the amount of financial leverage and the firm size.…”
Section: Introductionmentioning
confidence: 99%